Parametric Excitation of Ultracold Sodium Atoms in an Optical Dipole Trap - Ningxuan Zheng; Wenliang Liu; Jizhou Wu; Yuqing Li; Vladimir Sovkov; Jie Ma (Photonics, 2022)
Parametric modulation is an effective tool to measure the trap frequency and investigate the atom dynamics in an optical dipole trap or lattices. Herein, we report on experimental research of parametric resonances in an optical dipole trap. By modulating the trapping potential, we have measured the atomic loss dependence on the frequency of the parametric modulations. The resonance loss spectra and the evolution of atom populations at the resonant frequency have been demonstrated and compared under three modulation waveforms (sine, triangle and square waves). A phenomenological theoretical simulation has been performed and shown good accordance with the observed resonance loss spectra and the evolution of atom populations. The theoretical analysis can be easily extended to a complex waveform modulation and reproduce enough of the experiments.